ANALISIS FAKTOR EKSTERNAL DAN FAKTOR INTERNAL KETTNER DALAM ORGANISASI LAYANAN SOSIAL RIFKA ANNISA WOMEN CRISIS CENTER - Rizkiyah, Iin; Nulhaqim, Soni Akhmad (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The National Women's Commission states that Domestic Violence is always the most frequent case every year. Case data from Rifka Annisa also says that the number of violence against wives has always been the highest number of other cases of violence, namely 216 in 2017 which were successfully reported. The urgency of the case of violence against the earthquake has made the Rifka Annisa Women Crisis Center Institution must adapt to various changes in the environment and develop other strategies as needed. In this writing, Kettner's internal and external factors were explained to the Rifka Annisa institution. Internal speaking factors start from the vision-mission, Organizational Operating System, Organizational Plan, Human Resources, and Technology Resources, while external factors see economic, sociological, political and technological factors. Kettner sees that these internal and external factors influence each other so it is necessary to map so that the institution's consistency in achieving excellence in service is maintained. Here the research method uses literature studies from journals and scientific articles relevant to this study. The study shows that the Rifka Annisa Institute is very consistent with the vision, mission and objectives of the institution and is very progressive towards service programs for victims of domestic violence.